THE CONCEPT OF THE LUXURY BRANDING IN SAMSUNG GALAXY S6 EDGE SERIES THROUGH TRIADIC MODES OF SIGN - Tiyo Paksi; Samuel Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2017)
This thesis mainly deals with the iconisation of signs and naturalisation process in order to reveal the way Samsung Galaxy S6 Edge is naturalised as a luxury product. This thesis also involves analysis of the luxury branding concept through the analysis of a product which conceptualises its advertisement using the concept of luxury identifiers. The focus of the writer’s analysis is the advertisements themselves as the writer will use the triadic modes of signs, naturalisation process, and the concept of luxury identifiers which also involves process of signification, and metaphor in its analysis. Those theories will help the writer in analysing the meaning of the advertisement first, and then figure out the aim of the luxury branding strategy in the product, then figure out how the expressions are used in the luxury concept of advertisement. The writer analyses the advertisement of Samsung Galaxy S6 Edge which was published in 2015. From the analysis, the writer found out that the luxury branding strategy of Samsung Galaxy S6 Edge utilises naturalisation process to naturalise the luxury identity of Samsung Galaxy S6 Edge which is a masstige product. Using that as a basis, the expressions in the advertisement focus on selling the idea that Samsung Galaxy S6 Edge is a luxury product which is an innovative idea designed for professionals and to display superiority within the social group. Samsung Galaxy S6 Edge aims to provide the user with a display of social superiority within the social group through the consumption of Samsung Galaxy S6 Edge. In that regards, the user will be seen as a person who is wealthy, stand out in terms of taste, and a professional who is fully aware of the technology.